Pengaruh Perceived ease of Use, Digital Promotion, dan Social Influence terhadap Usage Decision QRIS Pada Generasi Z di Jabodetabek - Muhammad Raihan Rafiq Hermansyah; Nadya Fadillah Fidhyallah; Prima Andriani (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of perceived ease of use, digital promotion, and social influence on the usage decision of Quick Response Code Indonesian Standard (QRIS) among Generation Z in Jabodetabek. A quantitative approach with a causal research design was employed, involving 257 respondents selected using purposive sampling. Data were collected through online questionnaires and analyzed using IBM SPSS 31, including validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing. The findings indicate that perceived ease of use, digital promotion, and social influence have a positive and significant effect on usage decision, both partially and simultaneously. Digital promotion was identified as the most dominant variable influencing usage decision, followed by social influence and perceived ease of use. The coefficient of determination (Adjusted R²) showed that the three independent variables jointly explained 86.5% of the variation in usage decision, while the remaining 13.5% were explained by other factors outside the model, such as perceived security and trust. These findings support the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT), suggesting that the decision to use QRIS among Generation Z is driven not only by ease of use but also by promotional stimuli and social norms. This study contributes to the understanding of consumer behavior in the context of digital payment systems and provides practical insights for payment service providers and regulators in designing more effective strategies to encourage sustainable QRIS adoption